Pulse modulators for the VEPP-5 injection complex klystron power supply - Akimov, A.V.; Akimov, V.E.; Bak, P.A.; Kazarezov, I.V.; Kot, N.H.; Chupyra, A.G.; Rezakov, A.M.; Yudin, V.D. (Вопросы атомной науки и техники, 2001)
In the complex VEPP-5 preinjector the klystrons are supplied by the modulators with a pulse power of 150 MW, a voltage of 47.5 kV, a primary current of 6.3 kA and a pulse duration of 3.5 ms. During the long time operation some disadvantages in the design have been revealed and proper improvements were made. The modulator design with the taking into account all the resent changes is described and test results are presented. At present, three modulators are supplying three klystrons 5045 (production of SLAC Lab., USA) and the forth modulator is tested with a dummy load in the nominal mode of operation.